2019
DOI: 10.1002/jum.15002
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Superb Microvascular Imaging and Contrast‐Enhanced Ultrasonography in the Evaluation of Vascularization in Early Bone Regeneration

Abstract: Objective The aim of this study was to investigate value of superb microvascular imaging (SMI) and contrast‐enhanced ultrasonography (CEUS) in evaluating the neovascularization of early bone regeneration. Methods Twenty‐five Sprague‐Dawley male rats were implanted with recombinant human bone morphogenetic protein‐2/calcium phosphate cement (rhBMP‐2/) in the muscle space of the left hind limb near the femoral head to establish the rat model of intramuscular ectopic osteogenesis. Ultrasonography and pathologic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…The technique uses an adaptive wall filter that is different from conventional ultrasound and minimizes flash artifacts. In the absence of contrast media, SMI can improve the sensitivity of slow‐flow visibility and the signal detection of small blood vessels 29‐31 . SMI operates in two modes: color (cSMI) and monochrome (mSMI).…”
Section: Discussionmentioning
confidence: 99%
“…The technique uses an adaptive wall filter that is different from conventional ultrasound and minimizes flash artifacts. In the absence of contrast media, SMI can improve the sensitivity of slow‐flow visibility and the signal detection of small blood vessels 29‐31 . SMI operates in two modes: color (cSMI) and monochrome (mSMI).…”
Section: Discussionmentioning
confidence: 99%
“…They not only modulate trophoblast invasion by producing IL-8 and IL-10 but also initiate artery remodeling through secreting vascular endothelial growth factor (VEGF) and arginase-1 ( 5 , 6 ). dNK plays an important role in extravillous trophoblast (EVT) cells acquiring invasive phenotype and invasive EVT gaining endothelial-like properties ( 8 ). Decidual non-NK ILCs are mainly ILC3 and participate in tissue remodeling by expressing IL-22 and IL-8 or inducing decidual stromal cell (DSC) to express adhesion molecules ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, we further confirmed that melatonin treatment could accelerate bone repair and increase bone strength by promoting the osteogenesis and angiogenesis of tibia defect in OVX rats. Bone regeneration is inseparable from the supply of nutrients, and angiogenesis in bone is crucial for bone defect repair (37). Vascularization is the premise of bone defect repair (38), which is a key link in the process of fracture healing and bone defect repair (39).…”
Section: Discussionmentioning
confidence: 99%
“…Bone regeneration is inseparable from the supply of nutrients, and angiogenesis in bone is crucial for bone defect repair ( 37 ). Vascularization is the premise of bone defect repair ( 38 ), which is a key link in the process of fracture healing and bone defect repair ( 39 ).…”
Section: Discussionmentioning
confidence: 99%